قراءة في الجغرافيـا السياسيـة لكتاب أفريقيـا في القرن العشرين من خلال القارة المستعمرة - هلايلي, حنيفي (جامعة الوادي - University of Eloued, 2022)
تعد هذه الدراسة ترجمة مختصرة و مراجعة لكتاب المؤرخ الكونغولي إليكيا مبوكولو أفريقيـا في القرن العشرين من خلال القارة المستعمرة . حاول المؤرخ الكونغولي في كتابه أن يعيد قراءة منظومة البحث التاريخي لأفريقيا عبر قراءة مقارنة، من خلال تقديم مسرد تاريخي و جغرافي، حلل فيه الكتاب في تسعة فصول،أطرها بمؤشرات توضيحية ذات بعد جغرافي. كما عالج الكتاب تاريخ القارة الأفريقية مع التركز على هدفين إجرائيين هما: تحليل الأوضاع من الداخل بواسطة رصد المحطات الكبرى للمناطق الجغراسياسية للقارة . اعتمد الكاتب من خلالها على الأحداث التاريخية البارزة بطريقة تحليلية، ومن جهة أخرى طرح القضايا التي تعاني منها القارة وسط التحولات السياسية و الاقتصادية و الاجتماعية. و سجل في السياق نفسه مسألة هشاشة تعامل النظام الاستعماري مع الأفارقة. This study is a brief translation and review of the book of the Congolese historian Elikia M'Bokolo, Africa in the Twentieth Century through the Colonial Continent. In his book, the Congolese historian tries to re-read the system of historical research in Africa through a comparative reading, by presenting a historical and geographical glossary, in which the book is analyzed in nine chapters, framed by illustrative indicators with a geographical dimension. The book also dealt with the history of the African continent with a focus on two procedural objectives: analyzing the situation from the inside by monitoring the major stations of the continent's geopolitical regions, through which the writer relied on the prominent historical events in an analytical way, and on the other hand, raised the issues that the continent suffers from amid political and economic transformations and social. In the same context, he recorded the issue of the fragility of the colonial regime's dealings with Africans.
مقال
Keywords: أفريقيا ; الاستعمار الأوروبي ; القارة المستعمرة ; الجغرافيا السياسية; Africa; European colonialism; colonial continent; geopolitics